Object Detection Radar Prototype with Ultrasonic Sensor Using Iot-Based Arduino - wandynata Prima; Yo Ceng Giap (bit-Tech, 2021)
Internet of Things (IoT) is a concept that aims to expand the benefits of connected internet connectivity. Internet of Things (IoT) refers to objects that are uniquely identified as virtual reservations in an internet-based structure. At this time, the limitation of surveillance control in observing objects as negligence of the limitation of view, light conditions or obstructions becomes a problem in application and monitoring. The use of radar is one solution to overcome this condition. Radar stands for radio detection and range is a device whose function is to determine the distance, direction, or speed of a moving and fixed object. Radar can be used in mapping applications and exploration of objects in unknown space. The use of radar can also help navigate moving objects. In this study, a radar prototype with ultrasonic sensors and a simcard module was made that can provide notification via SMS if an object is near the radar. It is hoped that this radar prototype can be used to identify the location of the presence of obstructive objects in rooms with limited access or in dangerous areas